2014
DOI: 10.15590/ajhal/2014/v1i2/54051
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities to Implement Inclusive Education

Abstract: This study is conducted in order to assess the challenges and opportunities to implement inclusive education in selected primary schools of North GondarZone. In order to attain the objectives of the study, related literatures on international policies and concepts of inclusive education was reviewed in detail. Concerning the significance of the study it is expected that it will highlight those concerned individuals on the existing situation prevailing in connection with the problem under study and devise mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
11
0
3
Order By: Relevance
“…The study also found, the physical environment such as public places in schools to be unfriendly to empower the participation of students with disabilities (Gregorius, 2016;Ocloo & Subbey, 2008;Opoku et al, 2015Opoku et al, , 2016. It perhaps would have been better if schools received direct financial assistance from the government which they could use to address their contextual needs, this finding is in line with studies by Campos et al, (2014) and Mitiku et al, (2014). Without any financial support from the government, schools cannot do much to assist students with disabilities in terms of physical environment and infrastructure.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The study also found, the physical environment such as public places in schools to be unfriendly to empower the participation of students with disabilities (Gregorius, 2016;Ocloo & Subbey, 2008;Opoku et al, 2015Opoku et al, , 2016. It perhaps would have been better if schools received direct financial assistance from the government which they could use to address their contextual needs, this finding is in line with studies by Campos et al, (2014) and Mitiku et al, (2014). Without any financial support from the government, schools cannot do much to assist students with disabilities in terms of physical environment and infrastructure.…”
Section: Discussionsupporting
confidence: 63%
“…The above mentioned studies highlight an important complexity between operations, resourcing and training in inclusive education. Irrespective of these complexities, it is claimed that the challenges outweigh the benefits of inclusive education in terms of the overall benefit to the students and the wider community (Mitiku, Alemu, & Mengsitu, 2014). In terms of teacher training, the problem could be two fold.…”
mentioning
confidence: 99%
“…Perbedaan kebutuhan tersebut disebabkan oleh adanya keterbatasan fisik, emosi, perilaku, mental, dan sosial, maupun siswa yang berpotensi memiliki kecerdasan dan/atau bakat istimewa sehingga mereka berhak memperoleh pendidikan yang sesuai kebutuhannya dan (2) merealisasikan penyelenggaraan pendidikan dengan memerhatikan keberagaman serta tidak diskriminatif pada semua siswa seperti yang dimaksud pada pernyataan 1 di atas (Permendiknas, 2009). Sejalan dengan pandangan Pemerintah mengenai pendidikan inklusi, Disability in Ethiophia (dalam Mitiku et al, 2014) menekankan bahwa dalam pelaksanaan pendidikan inklusi berarti adanya penerimaan semua siswa di sekolah umum, tanpa ada diskriminasi. Perbedaan yang dimiliki siswa perlu disikapi secara positif sebagai bentuk keragaman.…”
Section: Pendahuluanunclassified
“…Inklusi bukan sekedar menempatkan siswa yang memiliki keterbatasan pada kelas utama. Namun, adanya pengakuan bahwa setiap anak memiliki kebutuhan khusus dan guru dilatih untuk memfasilitasi kebutuhan siswa di kelas inklusi (Tomlinson dalam Mitiku et al, 2014). Pelaksanaan pendidikan inklusif ini didasari oleh prinsip bahwa semua orang setara dan harus saling menghargai (IEAG dalam Martona, 2013).…”
Section: Pendahuluanunclassified
“…Analyzes the components of the implementation of IE consist of: 1) The process of identification and screening; 2) Individual Educational Program (IEP); 3) The physical environment of SNC to learn; 4) Methods and procedures of teaching in inclusive classroom [19].…”
Section: E Lack Of Facilities and Supportsmentioning
confidence: 99%